2013
DOI: 10.2109/jcersj2.121.156
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of barium titanate: fine particles and ceramics

Abstract: The size effect of ferroelectric materials is one of the most important issues to develop next-generation dielectric devices. In this paper, we reviewed our studies on the size effects of barium titante (BaTiO 3 ) fine particles and ceramics. In the size effect of BaTiO 3 fine particles, the maximum of dielectric permittivity was observed at a particle size of around 140 nm, and was explained by the composite structure model including a gradient lattice strain layer (GLSL) having a very high permittivity. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
128
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 51 publications
6
128
2
Order By: Relevance
“…[32,33] Earlier papers reported that the optimum grain size to achieve high dielectric constants was in the range of 700-1,300 nm. [2,3,5] However, this present work suggests that the optimum grain size can shift even to the nanometer level after severe straining. The increase in the dielectric constant by nanograin formation through HPT processing is consistent with the theoretical models based on elastic field energy and domain wall energy.…”
contrasting
confidence: 53%
See 4 more Smart Citations
“…[32,33] Earlier papers reported that the optimum grain size to achieve high dielectric constants was in the range of 700-1,300 nm. [2,3,5] However, this present work suggests that the optimum grain size can shift even to the nanometer level after severe straining. The increase in the dielectric constant by nanograin formation through HPT processing is consistent with the theoretical models based on elastic field energy and domain wall energy.…”
contrasting
confidence: 53%
“…Therefore, the increase in dielectric constant is not due to the effect of dielectric loss. The dielectric constant of 5,000-14,000 after N = 5 is higher than values reported in the literatures, [1][2][3][4][5] suggesting that the current material should be promising for high-capacitance capacitors and for electronic devices that need efficient mechanicalelectric energy conversion, provided that the material can be produced with a reasonable cost.…”
mentioning
confidence: 68%
See 3 more Smart Citations